Our Ways, Your Ways, Both Ways – a multi-disciplinary collaboration to develop, embed and evaluate a model of social and emotional wellbeing care for Aboriginal and Torres Strait Islander young people who experience detention – Phase 1 - Dale, Penny R.; Meurk, Carla; Williams, Megan; Watson, Marshall; Steele, Megan L.; Wittenhagen, Lisa; Harden, Scott; Stathis, Stephen; Scott, James G.; Kinner, Stuart; Heffernan, Ed (Frontiers in Psychiatry, 2023)
The National Strategic Framework for Aboriginal and Torres Strait Islander Peoples' Mental Health and Social and Emotional Wellbeing identifies building a strong Aboriginal and Torres Strait Islander led evidence-base to inform care as a key priority. Aboriginal and/or Torres Strait Islander adolescents in contact with the criminal justice system are a highly vulnerable group of Australians, with substantial unmet needs. There is limited evidence to inform culturally appropriate models of care that meet the social and emotional wellbeing needs of justice-involved Aboriginal and/or Torres Strait Islander adolescents. This project aims to develop, implement and evaluate an in-reach and This is a provisional file, not the final typeset article community transitional model of social and emotional wellbeing care for Aboriginal and/or Torres Strait Islander adolescents (10-17 years old) who experience detention through close engagement with Aboriginal and/or Torres Strait Islander youth, Elders, researchers, practitioners and community members, and by drawing on culturally informed practice and knowledge systems. The project is based on a multi-level mixed methods design, with a strong focus on ongoing project evaluation (based on the Ngaa-bi-nya framework) and co-design. Co-design is facilitated through culturally safe and trauma informed participatory processes based on development of strong partnerships from project initiative, design, implementation and evaluation. Application of the landscape domain of the Ngaa-bi-nya framework for Aboriginal and Torres Strait Islander program evaluation will be explored in Phase one. Aboriginal and Torres Strait Islander adolescents with experience in detention will be engaged through one-on-one interviews with data collection through the Growth and Empowerment Measure (GEM) Youth (which will be adapted from the adult version and validated as part of this study), the Kessler Psychological Distress Scale (K-10), questions around alcohol and drug use, and narrative interviews exploring experience. Qualitative data will be analysed using an inductive thematic approach, structured within the framework of the Ngaa-bi-nya landscape prompts. Quantitative data will be analysed using descriptive statistics to provide a profile of the cohort. Findings from Phase one will be used to inform the development of a model of social and emotional wellbeing care that will be implemented and evaluated in Phase two.